History of Emergence and Development of Industrial Design - Muxsinovich, Valijonov Toirjon (International Journal on Orange Technologies, 2023)
This article describes the history of the development of industrial design. Today, industrial design is a complex interdisciplinary design and artistic activity that combines technical and humanitarian knowledge, engineering and artistic thinking, and is aimed at forming an objective world on an industrial basis in a very wide “contact zone” with a person.